2006
DOI: 10.1002/jbm.a.30913
|View full text |Cite
|
Sign up to set email alerts
|

BMP‐7 and CBFA1 in allograft bone in vivo bone formation and the influence of γ‐irradiation

Abstract: An initial study showed that morselized human bone grafts were osteoconductive and osteoinductive when implanted in nude rat tibial window defects, and 25 kGy of gamma-irradiation significantly reduced those properties. The mechanism of the osteoinductivity and the influence of gamma-irradiation required further investigation. In this study we assessed the paraffin sections of seven morselized human bone grafts implanted into rat tibial defects for 3 weeks after being treated with 0, 15, or 25 kGy gamma-radiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 104 publications
0
8
0
Order By: Relevance
“…The suggested radiobiological mechanism of RT consists of a suppression of the transformation of the pluripotent mesenchymal cells into osteoprogenitor cells and osteoblasts [33]. Furthermore, experimental data revealed that γ-irradiation significantly reduces the expression of BMP-7 (bone morphogenic protein-7) and CBFA1 (core binding factor alpha 1) which play a key role in the cellular process of differentiation of osteoblasts and the consecutive formation of ectopic bone tissue [7]. Considering the large number of orthopedic procedures which are possibly associated with an increased risk for the development of clinically significant HO, it is surprising that only a low number of reports have been published providing information about the value of RT in sites other than the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…The suggested radiobiological mechanism of RT consists of a suppression of the transformation of the pluripotent mesenchymal cells into osteoprogenitor cells and osteoblasts [33]. Furthermore, experimental data revealed that γ-irradiation significantly reduces the expression of BMP-7 (bone morphogenic protein-7) and CBFA1 (core binding factor alpha 1) which play a key role in the cellular process of differentiation of osteoblasts and the consecutive formation of ectopic bone tissue [7]. Considering the large number of orthopedic procedures which are possibly associated with an increased risk for the development of clinically significant HO, it is surprising that only a low number of reports have been published providing information about the value of RT in sites other than the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…IHC was performed as described previously (Chen et al, 2007). Eight animals were sacrificed for IHC.…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%
“…Several authors report that gamma irradiation does not directly affect BMPs, but indirectly changes their performance by attacking their courier -the collagen molecules (24)(25)(26). A dose-dependent reduction in BMP-7 and CBFA1 expression in 3-week-postimplanted allografts have also been observed using immunohistochemistry (27). In this case, the reduction was much more significant at 25 kGy than 15 and 0 kGy.…”
Section: Discussionmentioning
confidence: 72%